PELATIHAN MANASIK HAJI PADA ANAK–ANAK: BENTUK PENANAMAN NILAI-NILAI AGAMA USIA DINI - Mufidah Yusroh; Ellyana Ilsan Eka Putri (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2019)
Understanding religious value for preliminary students could be done through Haj Training. Haj Training is the way to increase students’ understanding about religious value in order to make them know and understand the one and only so called Allah SWT. This haj training was done at school. Through this haj training, the first aim is to give understanding to all participants especially students of elementary school about how to practice hajj manasik. Thus, the descriptive qualitative was applied to this study in SDN 5 Genteng Wetan Banyuwangi and accompanied by college students of IAI Ibrahimy Genteng. Thus, the result showed that haj training had impact to the preliminary students of SDN 5 Genteng.